The Influence of Brand Perception, Social Influence, and Attitude to Functional Food on Repurchase Intention With Conspicuous Consumption as an Intervening Variable (Study on Kopi Kelana in Surabaya) - Aulia Life Rahma Putri; Nurul Azizah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of Brand Perception, Social Influence, and Attitude to Functional Food on Repurchase Intention, with Conspicuous Consumption as an intervening variable, in the context of Kelana Mobile Coffee in Surabaya. This study uses quantitative methods with purposive sampling techniques, where data is collected through questionnaires distributed to 100 respondents. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0. The results showed that Brand Perception has a significant effect on Conspicuous Consumption, but has no significant effect on Repurchase Intention. Meanwhile, Social Influence has no significant effect on Conspicuous Consumption or Repurchase Intention, which indicates that social recommendations do not directly influence repurchase decisions. On the other hand, Attitude to Functional Food has a significant effect on Conspicuous Consumption and Repurchase Intention, indicating that consumers who value the health benefits of a product are more likely to buy and consume the product as part of their lifestyle. In addition, Conspicuous Consumption has no significant effect in mediating Brand Perception on Repurchase Intention, but has a significant role in mediating the relationship between Social Influence and Repurchase Intention, as well as between Attitude to Functional Food and Repurchase Intention. This finding suggests that although conspicuous consumption does not always play a role in strengthening the relationship between brand perception and repurchase intention, this factor can strengthen the influence of social influence and attitude towards functional food in driving repurchase decisions.The results of this study provide implications for Kopi Keliling businesses that marketing strategies based on healthy lifestyles and social trends can be an effective approach to increase customer loyalty and encourage repurchases.